O Departamento Peixe/Pesca - Resende, Emiko Kawakami de; Carvalho, Francisco Martinho; Castelo, Francisco Pereira; Soares, Maria Gercilia Mota; Almeida, Raimunda Gonçalves de; Annibal, Sérgio Roberto Pereira; Best, Robin Christopher; Thatcher, Vernon Everet (Acta Amazonica, 1981)
This paper concerns about the historic of the Fish/Fishery Department development at INPA - Instituto Nacional de Pesquisas da Amazônia. Now a day, this Department is formed by six divisions. The Division of Fishery do the evaluation of the fish stock ay using catch and landing data, field observations on catch methods, behaviour of fishing fleet, etc... The Division of Fish Biology takes place on systematic characterization of amazonian fish species, the study of food and feeding habits and reproduction according to the annual water level cycling, the differences on fish fauna related to the main types of water, as well as parasitology and icthyopathology. The Division of Aquatic Ecology analyses the limnological data of lakes and rivers of the amazonian region related to different types of water; special attention has been given to aquatic macrophites and its potential utilization in agriculture as fertilizer and cattle food. The Division of Fish Technology analyses the chemical composition of regional fishes, it develops preservation methods like as salting, drying and curing as well as quality control standards. The Division of Fish Culture develops culture methods of regional fishes, the study of natural and artificial ways of reproduction and experiments with different food formulations. The Division of Aquatic Mammals studies the biology, ecology and physiology of peixe-boi (manatee) and two species of river dolphins.